2018
DOI: 10.1177/0954406218763447
|View full text |Cite
|
Sign up to set email alerts
|

The machining characteristics and surface integrity of Ni-rich NiTi shape memory alloy using wire electric discharge machining

Abstract: Owing to the increasing demand for Ni-rich shape memory alloys in various sectors such as biomedical, aerospace, and robotics, the efficient machining of shape memory alloys is vital for their productive exploitation. The aim of this experimental investigation is to explore the influence of wire electric discharge machining process parameters such as spark gap voltage, wire tension, spark off time, wire speed, and spark on time, on the cutting efficiency and surface roughness of Ni50.89Ti49.11 SMA using one fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Spark frequency (number of sparks per second) is given according to Eq. (3) [6] which increases with the decrease in t ON . Here t ON is pulse on time, the five levels of t ON , 105, 100, 115, 120, and 125 µs, and pulse off time (t OFF ), 52, 55, 57, 60, and 63 µs, were considered during experiments.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Spark frequency (number of sparks per second) is given according to Eq. (3) [6] which increases with the decrease in t ON . Here t ON is pulse on time, the five levels of t ON , 105, 100, 115, 120, and 125 µs, and pulse off time (t OFF ), 52, 55, 57, 60, and 63 µs, were considered during experiments.…”
Section: Methodsmentioning
confidence: 89%
“…Currently, SMAs are being widely used in various sectors, such as robotics, biomedical, aerospace, and other important industries due to their outstanding properties [2,3]. Ni-rich NiTi SMAs show better superelasticity and shape memory effect compared to equiatomic NiTi SMAs because of higher intrinsic strength, and they can be precipitation-hardened [4][5][6]. Conventional machining of NiTi SMAs is the most challenging task because of the high reactivity of titanium which causes poor surface finish, high tool wear, and high machining time [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High pulse-on time and high discharge current in WEDM meant high discharge energy and as a result of that a large chance of cracks, globules and other surface defects [28,29]. However, with the increase in pulse-off time, discharge energy and spark intensity decreased, which resulted in a reduction in cracks and surface defects [30]. Integrity is key in many applications in high-performance alloys [31].…”
Section: Scanning Morphologymentioning
confidence: 99%
“…Elemental analysis was carried out by using energy dispersive X-ray (EDX)analysis. The researchers used a brass wire as a tool electrode, and reported that the element of the wire material was deposited on the surface of the machined surface [28,30]. Figure 9 shows the result of EDX analysis for the machined sample obtained at the optimized parameter settings.…”
Section: Scanning Morphologymentioning
confidence: 99%